Antibody therapy for COVID-19. Issue 6 (December 2021) - Hammarström, Lennart; Marcotte, Harold; Piralla, Antonio; Baldanti, Fausto; Pan-Hammarström, Qiang
Abstract : Purpose of review: To provide an update of the current state of antibody therapy for Severe Acute Respiratory Syndrome Coronavirus 2 infection that has progressed immensely in a very short time period. Recent findings: Limited clinical effect of classical passive immunotherapy (plasma therapy, hyperimmune immunoglobulin [IgG] preparations) whereas monoclonal antibody therapy, if initiated early in the disease process, shows promising results. Summary: Although antibody therapy still remains to be fully explored in patients with COVID-19, a combination of IgG monoclonal antibodies against the receptor-binding domain of the spike protein currently appears to provide the best form of antibody therapy, Immunoglobulin A dimers and Immunoglobulin M pentamers also show promising preliminary therapeutic results.